Hantavirus infection in clinically suspected dengue fever patients - Praseno Hera Nirwati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2008)
Background: Hantavirus has been found in many parts of the world, including newly isolated virus in Indonesia. Although infection with the virus can result in specific signs and symptoms known as hemorrhagic fever with renal syndrome (HFRS), clinical presentation of the disease may be similar to those of dengue or other viruses infection. Diagnosis of both dengue and hantavirus infection should be established by laboratory test for the detection of specific antibodies.Objective: The aim of this study was to determine the presence of hantavirus infection in patients suspected to have dengue fever.Methods: Sera were prepared from venous blood of patients. Specific IgG and IgM anti hantavirus in sera from clinically suspected dengue fever patients were examined by an indirect immunoflourescence antibody technique.Results: Eight percent of sera samples were positive for both specific IgG and IgM anti hantavirus, whereas 1 2 percent of samples were positive for IgG only.Conclusion: It is concluded that the recent infection with hantavirus have been found in 8 percent of clinically suspected dengue fever patients, whereas 12 percent of the patients were infected with the virus some time in the past.Key words: hantavirus - immunofluorescence antibody technique - dengue fever - specific IgG and IgM anti hantavirus